A STUDY OF CLIL-BASED METHODOLOGY AND LANGUAGE SKILL DEVELOPMENT: A STUDY OF CLIL-BASED METHODOLOGY AND LANGUAGE SKILL DEVELOPMENT - Arzieva, Bibisanam (Журнал иностранных языков и лингвистики, 2025)
This study investigates the integration of Content and Language Integrated Learning (CLIL) within the regional education system of Karakalpakstan, with a particular focus on the development of English language competencies. Situated at the crossroads of multilingual education and ongoing educational reforms, Karakalpakstan presents unique challenges and opportunities for the implementation of the CLIL methodology. The research is based on a comprehensive dataset comprising qualitative interviews, classroom observations, and document analysis conducted across various schools and higher education institutions. The analysis of this data enabled the identification of key methodological practices, institutional constraints, and locally adapted CLIL strategies. The findings highlight the potential of CLIL to enhance students’ English proficiency, particularly when supported by targeted teacher training, contextually relevant materials, and cross-institutional collaboration.